Antioxidant Potential of Penicillium citrinum and its Optimization through Different Statistical Approaches - Chandra, Priyanka; Arora, Daljit Singh (Free Radicals and Antioxidants)
Three-step optimization strategies were applied to optimize the antioxidant potential of Penicillium citrinum. Primarily, different carbon and nitrogen sources were screened by classical methods, which revealed sucrose and NaNO3 to be the most suitable. Significance of the components of Czapek dox’s medium with respect to antioxidant activity was evaluated with Plackett-Burman design, which supported sucrose and NaNO3 to be the most significant. In second step, sucrose and NaNO3 along with temperature were further taken as three variables for response surface methodology to study their interaction. Response surface analysis showed 4% sucrose, 0.05% NaNO3 and incubation temperature of 35o C to be the optimal conditions. Under these conditions, the antioxidant potential assayed through different procedures was 90.1%, 70.9% and 70.1% scavenging effect for 1,1-diphenyl-2-picryl hydrazyl radical, ferrous ion and nitric oxide ion, respectively. The reducing power showed an absorbance of 1.35 with 65.5% activity for ferric reducing antioxidant power assay.
Keywords: Antioxidant activity; Penicillium citrinum; Plackett-Burman design; Response surface methodology (RSM); Total phenolic content